An efficient detection model of selective forwarding attacks in wireless mesh networks - Khanam, Shapla; Saleem, Habibullah Yusuf; Pathan, Al-Sakib Khan (Springer-Verlag, Berlin, Germany, 2012)
Wireless communications technologies have seen a great degree of advancements and sophistication in the past decade. Different research works have tried to solve various issues related to different wireless Ad hoc networks, many of which are yet to find standardized solutions. Among different classes of Ad hoc networks, Wireless Mesh Networks (WMNs) are becoming a popular choice now-a-days, which offer flexible, fast and inexpensive connectivity for communities, homes, municipalities, and other similar premises. While different research issues are being extensively dealt with for WMN, security flaws and attacks are turning out to be a significant concern as relatively less attention has been dedicated to this topic so far by the research community. Because of the structural formation and mode of operation of WMN, routing security is one of the prime concerns in WMN. An efficient method of detecting selective forwarding attack could largely ensure better and secure routing for which we have taken this as our research motivation. In this paper, we present a model for detecting selective forwarding attacks with a game theory-based approach to analyze the attack model, where the main goal of player 1 is to maximize its throughput and the goal of player 2 is to minimize the throughput of network. In our approach, we also propose a multi-hop acknowledgement based algorithm to analyze and detect the malicious behavior to defend against selective forwarding attacks in WMNs. We present our mathematical model and analyze it in detail to illustrate the efficiency of the proposed approach.